2011
DOI: 10.1016/j.jaridenv.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and socio-economical thresholds of land and plant-community degradation in semi-arid Mediterranean areas of southeastern Spain

Abstract: a b s t r a c tThe climate of semi-arid Mediterranean areas is characterized by highly variable rainfall and seasonal droughts, which favor highly specialized flora, high biodiversity, and the emergence of a large number of endemic species. Such highly specialized complex ecosystems are expected to be more difficult to return to a previous state following perturbation than are more mild ecosystems and lead to dramatic transitions in vegetation. An understanding of the circumstances under which irreversible tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 103 publications
1
40
0
Order By: Relevance
“…The large-scale study presented here identifies the main features of vegetation changes in the world's semiarid regions, but cannot provide details of particular processes identified at regional or local scales, some of which are highly complex. These include processes observed in Mediterranean regions, in which the magnitude of the response of the vegetation to drought is very sensitive to differences among sites, seasons, and species, but also to interactions with different environmental factors that determine plant conditions [84,85], and where centuries of significant human pressure have interacted with climate change and drought to produce mosaics of land degradation processes [17,19].…”
Section: Vegetation Activity Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large-scale study presented here identifies the main features of vegetation changes in the world's semiarid regions, but cannot provide details of particular processes identified at regional or local scales, some of which are highly complex. These include processes observed in Mediterranean regions, in which the magnitude of the response of the vegetation to drought is very sensitive to differences among sites, seasons, and species, but also to interactions with different environmental factors that determine plant conditions [84,85], and where centuries of significant human pressure have interacted with climate change and drought to produce mosaics of land degradation processes [17,19].…”
Section: Vegetation Activity Trendsmentioning
confidence: 99%
“…Nevertheless, some studies have shown that in semiarid regions characterized by soil limitations and intense human pressure, drought intensification as a consequence of warming processes may trigger land degradation processes [17]. These may be irreversible in areas in which edaphic conditions markedly limit vegetation establishment and development [18,19], even with the application of ecological restoration practices [20].…”
Section: Introductionmentioning
confidence: 99%
“…This ecosystem type is widespread in the western Mediterranean region: in Cabo de Gata-Níjar Natural Park, a large fraction of agricultural areas that were abandoned over 1957-1994 resulted in espartal ecosystems (Alados et al, 2004(Alados et al, , 2011. The functioning of both experimental sites can be divided into two main periods.…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
“…In this sense, mitigation policies to confront land degradation should be focused on prevention programs since ecosystem restoration does not recover complete ecosystem functionality (Lal, 2001;Moreno-Mateos et al, 2017). Moreover, even after several decades, relict degradation legacies can remain (Alados et al, 2011).…”
Section: Amoladerasmentioning
confidence: 99%
“…A report by the International Commission on Irrigation and Drainage [71] finds that dam construction significantly increases agricultural production and yield besides enabling farmers to substitute towards water-intensive crops. However, irrigated marginal lands in Spain are largely degrading due to increased extensive agriculture and population expansion is noted in [72]. We identify an urgent need to seek alternative sustainable sources of water, and investigations on water harvesting technologies that can benefit the sector to avoid resource exhaustion.…”
Section: Significant Predictorsmentioning
confidence: 99%